Improving Student Learning Outcomes Through the Problem Based Learning Model with The Help of The Natural Resource Board - Nurcahyo, Roffy; Farokhah, Innalatul; Sari, Alif Nurdiana; Maulidiyah, Nur Azizatul; Ardianti, Sekar Dwi (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study seeks to find out how much better the PASUDA (Resource Board) learning media can become by using the problem-based learning model to improve the learning results of Grade V students at SD 1 Jekulo Kudus. We conducted the study because the students appeared passive and had poor learning processes and outcomes. As a result, researchers used a learning model assisted by media to improve learning. This study is classroom action research. Students registered in grade V at SD 1 Jekulo, totalling 32 people, are the subjects of this study. Research Methods: This research method employs a classroom action research approach that consists of two cycles, which include the steps of observation, reflection, and implementation of actions. Researchers work together with direct observers during the action and evaluate students' abilities. Finding/Results: Data analysis shows an increase in students' learning outcomes through student learning completeness in cycle I (62.5%) and cycle II (82.25%). The average student learning outcomes increased, as indicated by 60.5% of students who were active in cycle I and 80.75% in cycle II. Conclusion: The study indicated that students in grade V of SD 1 Jekulo can improve their science learning outcomes by using the problem-based learning model assisted by PASUDA media (resource board).